Luminal chemosensing and upper gastrointestinal mucosal defenses(1)(2)(3)(4) - Akiba, Yasutada (American Society for Nutrition, 2009)
The upper gastrointestinal mucosa is exposed to endogenous and exogenous substances, including gastric acid, carbon dioxide, and foodstuffs. Physiologic processes such as secretion, digestion, absorption, and motility occur in the gastrointestinal tract in response to ingested substances, which implies the presence of mucosal sensors. We hypothesize that mucosal acid sensors and tastelike receptors are important components of the mucosal chemosensing system. We have shown that luminal acid/carbon dioxide is sensed via ecto- and cytosolic carbonic anhydrases and ion transporters in the epithelial cells and via acid sensors on the afferent nerves in the duodenum and esophagus. Furthermore, a luminal l-glutamate signal is mediated via mucosal l-glutamate receptors with activation of afferent nerves and cyclooxygenase in the duodenum, which suggests the presence of luminal l-glutamate sensing. These luminal chemosensors help to activate mucosal defense mechanisms to maintain the mucosal integrity and physiologic responses of the upper gastrointestinal tract. Because neural pathways are components of the luminal chemosensory system, investigation of these pathways may help to identify novel molecular targets in the treatment and prevention of mucosal injury and visceral sensation.